The fate of CdS quantum dots in plants as revealed by extended X-ray absorption fine structure (EXAFS) analysis. Issue 4 (24th March 2020) - Marmiroli, Marta; Lepore, Giovanni Orazio; Pagano, Luca; d'Acapito, Francesco; Gianoncelli, Alessandra; Villani, Marco; Lazzarini, Laura; White, Jason C.; Marmiroli, Nelson
Abstract : The use of quantum dots (QDs) is widespread and as such, the potential risk associated with their dispersion in the environment has stimulated research on their interaction with potential sensitive receptors. Abstract : The use of quantum dots (QDs) is widespread and as such, the potential risk associated with their dispersion in the environment has stimulated research on their interaction with potential sensitive receptors. To this end, the model plant Arabidopsis thaliana wild type (wt) and two mutant lines known to be tolerant to cadmium-based CdS QDs but not to CdSO4 were exposed to CdS QDs or CdSO4 at sub-inhibitory concentrations for 20 days. X-ray absorption spectroscopy (XAS) was employed to investigate cadmium speciation in the cellular environment of the plants after treatment. After exposure to CdS QDs and CdSO4, differences in biomass were observed between the wt and mutants, but the form of Cd in the treatment had a marked influence on the cadmium atomic environment. The spectra of whole plant samples were found to be compatible with a mixed O/S coordination; while Cd–S distances did not show much variation, Cd–O distances varied from ≈2.16 Å in samples grown with QDs to ≈2.22 Å in those grown with CdSO4 . In addition, the number of Cd–S bonds in plants grown with QDs was higher than Cd–O bonds. XAS data showed that CdS QDs were bio-transformed after their uptake; the particle original structure was modified but not totally eliminated, and Cd atoms were not released as Cd(ii ) ions. These findings show the nanoscale specific response of plants to QDs, provide important insight into understanding the nanoparticle fate in plants and in the environment, and have implications for both risk assessment and design of appropriate remediation strategies.